Development of Interactive Electronic Practicum Module by Utilizing Tracker Software - Ismu Wahyudi; Eko Suyanto; Hervin Maulina (Jurnal Pembelajaran Fisika, 2022)
This study aims to develop physics practicum module for straight motion material in order to make student are able to do practicum independently at home or school by utilizing free-acces tracker software to obtain the data with various features and user flexibility. This study was research and development, which were consisted of four stages; there were Design, Development, Implementation, and Decision Making. The data of this study were obtained from questionnaires from the expert’s validation and small group tests, which were then analyzed quantitatively descriptively. The results of the research analysis show that the developed interactive electronic practicum module has been validated, feasible, and effectively used in learning. In addition, this module is also very effective in training students' multiple representation skills and quite effective in training students' graphic interpretation skills.Keywords: Interactive electronic practicum module, Straight motion, Tracker softwareDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202205